The Construction of Masculinity in the “Typing Ganteng” Phenomenon on TikTok - Achmad Hidir; Rahman Malik; Tengku Romi Marnelly; Ferdo Ferdo; Abdillah Habibi (Indonesian Language Education and Literature, 2025)
The phenomenon of ”typing ganteng” on social media, particularly TikTok, demonstrates that constructions of masculinity can be shaped through digital language styles. This study aims to explore how the ”typing ganteng” style, popularized by influencers and content creators on TikTok, shapes representations of masculinity. The method used was descriptive qualitative content analysis, utilizing purposive data from TikTok accounts producing content related to this phenomenon. The results show that through ”typing ganteng” content, influencers can establish standards of digital masculinity, as evidenced by stylistic characteristics such as the use of lowercase letters at the beginning of sentences, prolonged vowels, concise typing, and controlled humor. This style of language is considered attractive and masculine by women on social media, encouraging other users to imitate and conform to established norms. Findings indicate that the concept of masculinity in the digital age has shifted from traditional norms to new forms displayed through written interactions on social media. This study demonstrates that language functions as a cultural product that continues to evolve according to social expectations, enabling young men to display and negotiate masculine identities online. The study also highlights that perceptions of masculinity are relative; some male users adopt “typing ganteng” styles to gain social recognition, while others view masculinity as more flexible and individual. This research is expected to enrich sociolinguistic research and provide deeper insights into the relationship between language, gender, and social media culture.Konstruksi Maskulinitas dalam Fenomena “Typing Ganteng” di TikTokFenomena “typing ganteng” di media sosial, khususnya TikTok menunjukkan bahwa konstruksi maskulinitas dapat dibentuk melalui gaya bahasa digital. Penelitian ini bertujuan untuk mengeksplorasi gaya “typing ganteng” yang dipopulerkan oleh influencer dan pencipta konten di TikTok dalam merepresentasikan maskulinitas. Metode penelitian menggunakan kualitatif deskriptif dengan memanfaatkan data purposif dari akun TikTok yang menghasilkan konten terkait fenomena ini. Hasil penelitian menunjukkan bahwa melalui konten “typing ganteng”, influencer dapat menetapkan standar maskulinitas secara digital, melalui penggunaan huruf kecil di awal kalimat, vocal yang diperpanjang, pengetikan yang ringkas, dan humor. Gaya bahasa ini dianggap menarik dan maskulin oleh Wanita di media sosial sehingga mendorong pengguna lain untuk meniru dan mematuhi norma tersebut. Temuan penelitian menunjukkan bahwa konsep maskulinitas di era digital telah bergeser dari norma tradisional ke bentuk baru yang ditampilkan melalui interaksi tertulis di media sosial. Penelitian ini menunjukkan bahwa bahasa berfungsi sebagai produk budaya yang terus berkembang sesuai dengan harapan sosial sehingga memungkinkan laki-laki menampilkan dan menegosiasikan identitas maskulin secara daring. Studi ini juga menyoroti bahwa persepsi maskulinitas bersifat relatif. Beberapa pengguna laki-laki mengadopsi gaya “typing ganteng” untuk mendapatkan pengakuan sosial sementara yang lain memandang maskulinitas sebagai sesuatu yang fleksibel dan individual. Penelitian ini diharapkan dapat memperkaya penelitian sosiolinguistik dan memberi wawasan yang lebih dalam tentang hubungan antara bahasa, gender, dan budaya di media sosial.